Customer focus and core competencies are critical traits in new economic (impact) - Krupa, Kazimierz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2007)
New economy relations differ from inter-regional economic new global relations (i.e., the economic new relations among different parts of the same nations), thus requiring somewhat different tools of analysis and justifying new economy as a distinct branch of economics. That is, nations usually impose some restrictions on the flow of goods, services, and factors across their borders while generally imposing no such restrictions internally. In addition, global flows are to some extent hampered by differences in language, customs, and laws. Future, international global flows of goods, services and resources give rise to payments and receipts in foreign currencies, which change in value over time.

W dobie globalizacji i w czasie funkcjonowania instrumentów nowej ekonomii agresywna rywalizacja o klienta determinuje rozwiązania we wszystkich podmiotach zorganizowanych. Można wyróżnić listę krytycznych przedsięwzięć koniecznych do akceptacji w operatywnym działaniu tych podmiotów oraz zestaw instrumentów, których zastosowanie może pozwolić firmom na „ucieczkę do przodu”.
Kompetencje i preferencje klientów głównymi determinantami nowej ekonomii